Squamous Cell Carcinoma in a Cat - Treatment with Metronomic Chemotherapy - Chalco Torres, Lorena Elizabeth; Guerrero Lopez, Ana Elizabeth; Sánchez Prado, Robert Gustavo; Apolo Arevalo, Guido Manuel; de Souza Pires, Claudina Rita (Acta Scientiae Veterinariae, 2023)
Background: Squamous cell carcinoma (SCC) is a malignant neoplasm associated with prolonged exposure to ultraviolet light and lack of skin pigment in white-coated animals. The disease diagnosis is based on the animal's history, clinical signs and histopathology of the samples collected. The therapeutic alternatives are diverse. Among them, one of the most used is the metronomic chemotherapy which is based on the use of cytostatics drugs, applied in low and frequent doses for a longer period of time. One of the mechanisms of action of this type of therapy is the decrease in angiogenesis. Non-steroidal anti-inflammatory drugs (NSAIDs) are simultaneously used to maximize the angiogenic effect. The objective of this study is to report the results of a treatment accomplised with metronomic chemotherapy (cyclophosphamide with meloxicam) in a domestic feline which presented a squamous cell tumor. Case: A 7-year-old female cat, mixed breed, not neutered, weighing 3.5 kg, was assisted at the Veterinary Specialties Teaching Clinic (CEEV) of the Technical University of Machala (UTMACH), presenting bilateral ulcerative lesion in the nasal plane for 5 months. Chronic exposure to sunlight is referred to in the patient's anamnesis. Aspiration cytology performed in the patient revealed an inflammatory process with a predominance of neutrophils and macrophages, and showed absence of neoplastic cells. A treatment based on antibiotics and corticosteroids was adopted. As there were no favorable results, an excisional biopsy procedure was chosen to collect the affected tissues. The result of the histopathological analysis was a level 2 squamous cell carcinoma (SCC). The initial treatment consisted of surgical removal of the tumor and later the use of metronomic chemotherapy based on Cyclophosphamide, Meloxicam, DHA (docosahexaenoic acid) and Sucralfate for 5 months was adopted. At the beginning of the second phase of treatment, the patient developed a macula that progressively diminished. Currently, the patient does not have any recurrence of the diagnosed neoplasm. Discussion: The diagnosis of squamous cell carcinoma was based on clinical and histopathological findings. The macroscopic lesions were crusted ulcers that do not heal in the nasal plane and auricular pavilion, as reported in the literature. SCC is characterized by the infiltration of squamous cells in the dermal layer of the skin, forming epithelial islands with keratin pearls. The histopathological findings of this case present the same characteristics. The climatic conditions of Ecuador, high temperatures with greater incidence of sunlight, hypopigmented areas of the animal's body and chronic exposure to solar radiation are risk factors present in this case that foster the development of this malignant neoplasm. There are multiple treatments to be introduced in this sort of pathology. In this case, surgical removal of the tumor was adopted, followed by metronomic chemotherapy based on cyclophosphamide at 10 mg/m2 and meloxicam at a 0.05 mg/kg per day for a period of time of five months, obtaining favorable results and absence of recurrence. Despite metronomic chemotherapy being easy to administer, with fewer side effects, which includes a better acceptance of care takers who are reluctant to administer conventional chemotherapy, further studies are still necessary in what concerns certain variables such as age, carcinoma level, appropriate dosages and drugs according to each neoplasm. Keywords: skin neoplasm, cytostatic drugs, feline. Título: Carcinoma de células escamosas em gato - tratamento com quimioterapia metrônica. Descritores: neoplasia da pele, droga citostática, felino.